Bcl‐2/Bcl‐xl inhibitor APG‐1252‐M1 is a promising therapeutic strategy for gastric carcinoma. (28th April 2020) - Yi, Hanjie; Qiu, Miao‐Zhen; Yuan, Luping; Luo, Qiuyun; Pan, Wentao; Zhou, Suna; Zhang, Lin; Yan, Xianglei; Yang, Da‐Jun
Abstract: Gastric carcinoma is the third major cause of cancer‐related death in China. Bcl‐2 and other BH3 family proteins are critically important in the process of apoptosis pathway, which may be a promising target. APG‐1252‐M1 specifically connects to Bcl‐2 and Bcl‐xl. The antitumor effect of APG‐1252‐M1 in six gastric cancer cells was identified by the Cell Counting Kit‐8 assay. The expression level of proapoptotic proteins was evaluated by Western blot. Meanwhile, the cell cycle and apoptosis distributions were analyzed by flow cytometry and JC‐1. Xenograft models were used to investigate the roles of APG‐1252‐M1 in suppressing the growth of tumors and enhancing the chemotherapy antitumor effect. The antitumor effect of APG‐1252‐M1 was time‐ and dose‐dependent and acted by initiating apoptosis. The change of cell cycle distribution was not discovered in gastric cancer cells treated with APG‐1252‐M1. APG‐1252‐M1 also exhibited synergy with chemotherapy in vivo. The combined group inhibited xenograft tumor growth more obviously than the other groups. Moreover, Ki‐67 was remarkably decreased in the combination group compared to other groups. In conclusion, APG‐1252‐M1 had a strong antitumor effect by inducing apoptosis and was synergistic with chemotherapy. Abstract : APG‐1252‐M1 is a new Bcl‐2/Bcl‐xl inhibitor. APG‐1252‐M1 both alone and in combination with chemotherapy exhibited antitumor effects though the intrinsic mitochondrial pathway of apoptosis in gastric cancer.